Thomas Reed. Un arquitecto del siglo XIX - Saldarriaga, Alberto (2015)
Thomas Reed, who was born in 1817 in the Tortola Island, in the Caribbean, and passed away in Daule, Ecuador in 1878, worked as an architect and engineer in Venezuela, Colombia and Ecuador between 1843 and 1878. Most of his works were requested by the governments of these three countries, and some of them are renowned for their exceptional quality at the time. That is why his name always appears in textbooks regarding the history of architecture in the 20th century in these three countries, and in each of them he is appreciated in a diﬀerent way. Thomas Reed was an architect of his time with a solid academic background. He was also a talented engineer, well versed in structural principles and management of materials. Among his works, the most exceptional ones include the San Pablo Theater in Caracas, which was never built; the National Capitol and the former Panopticon, which is now the National Museum of Colombia in Bogotá; the Panopticon and School of Fine Arts in Quito, and the Jambelí Bridge in Ecuador. His work, inspired on the historicism of the 19th century, does not reﬂect nostalgia, but rather the way of thinking during his time. The historical time of his work is the present.